CO2 storage potential and trapping mechanisms in the H-59 block of Jilin oilfield China. (June 2016) - Zhang, Liang; Li, Xin; Ren, Bo; Cui, Guodong; Zhang, Yin; Ren, Shaoran; Chen, Guoli; Zhang, Hua
Highlights: Factors k1 and k2 are introduced to indicate CO2 sweep efficiency in thin-layer oil reservoir. Effective CO2 storage capacity in the H-59 block is expected to be 26.37 × 10 4  ton. Up to June 2014, 21.08 × 10 4 ton of CO2 has been injected with over 95% stored. Geological structure decides injected CO2 mainly moving along the horizontal direction. 42.68–60.15% of the stored CO2 has been trapped by structure trapping mechanism. Abstract: A CO2 EOR and storage pilot test have been conducted in the H-59 block of Jilin oilfield China for well seven years. It is important to track the CO2 storage and distribution in the reservoir, which can provide valuable guidance for the operation in the next stage of the project. In this paper, the CO2 storage capacity in the H-59 block was calculated by considering various CO2 trapping mechanisms, and the distribution and trapping status of the stored CO2 were evaluated by using the reservoir simulation method. The effective CO2 storage capacity in the H-59 block is estimated to be 26.37 × 10 4  ton by incorporating the CO2 sweep efficiency and neglecting the mineral trapping. Up to June 2014, 21.08 × 10 4 ton of CO2 has been injected with over 95% stored. The geological structure of the H-59 block controls most of the injected CO2 moving only along the horizontal direction in the thin oil layers. The shape and size of the CO2 plume are mainly determined by the reservoir heterogeneity, well pattern and injected CO2 amount. According to the assessment results, the CO2 sweep efficiency within each well group varies from 20% to 80%. About 42.68–60.15% of the stored CO2 has been trapped at supercritical state accompanied with 24.85–41.8% and 15% of the stored CO2 dissolved in residual oil and water, respectively. The H-59 block still has a potentially remaining capacity of 6.25 × 10 4 ton of CO2 for the future storage. Necessary engineering measures might be taken to further increase the sweep and displacement efficiencies of CO2 to achieve this purpose.